A Vibration and Crack Assessment on Precast Pre-stressed Hollow-Core Floor - Abd Ghafar, Nor Hayati; Goh, Lyn Dee; Mohamad, Noridah; Seyed Hakim, Seyed Jamalaldin (International Journal of Integrated Engineering, 2024)
Hollow core concrete floors are usually used in high-rise buildings, shopping malls and parking garages due to their sustainability advantage in the construction industry. However, in certain conditions, hollow core concrete floors can be sensitive towards vibration due to long span. The floor vibration issue is crucial and must be managed properly during the building design phase, as addressing this issue becomes significantly more challenging after the structure has been constructed completely. Thus, this study aims to determine the vibration and crack behaviour of precast hollow core concrete floors. 3D finite element models of the floor were developed using SAP2000 software to obtain the vibration parameters of the hollow core concrete floor subjected to vehicle-induced vibration. The specifications of the floor materials are based on the hollow core concrete floor manufacturer, Eastern Pretech, and the acceleration time history from testing was applied to the analysis. Modal analysis and time history analysis were analysed to investigate the vibration behaviour of the hollow core concrete floor. Modal analysis revealed a fundamental frequency of 23.52 Hz for the floor with actual dimensions. The fundamental frequency of the floor was compared to the standard guideline for human vibration sensitivity, which is 10 Hz. Time history analysis was employed to assess floor deformation based on the vibration waves generated by vehicle movement on the floor. The crack assessment analysis on concrete topping of precast hollow core slab in the warehouse flooring system was carried out. The cracks that appeared on the concrete topping were investigated using vibration testing and finite element analysis. Acceleration data from the damaged area was captured and transformed into the frequency domain using ME’Scope to analyse the natural frequency behaviour. The preliminary finite element analysis was performed by SAP 2000 software. Normal attenuation was observed on the surface with a crack at 50 mm, as the pattern of the time series data at this location was similar to other sensor positions. Analysis of the frequency domain of the wave confirmed this observation, revealing a dominant frequency of 23.741 Hz and no abnormal event occurred during testing on the surface crack.